Pengembangan multimedia interaktif berbantuan canva dalam materi transformasi geometri kelas VIII SMP - Sumarno, Mahmuda; Suratman, Dede; T, Ahmad Yani; Siregar, Nurfadilah (IKIP Siliwangi, 2024)
This research aims to produce products in the form of interactive multimedia-based math learning media. Interactive multimedia-based math learning media used in this study uses the Canva application which contains gerometric transformation material. This research is a development research (research and develpoment) with the 4D approach. The subjects in this study were VIII grade students of SMP Negeri 13 Pontianak. The data in this study were obtained from a validation sheet instrument that would be assessed by material experts, media experts, and VIII grade students of SMP Negeri 13 Pontianak. The data obtained from this research is in the form of assessment scores which are categorized, then the media development is described. The data obtained from this research will be analized with descriptive statistics. The results of media development in this study obtained an average score of 3.45 with a very good category by material experts and media experts. While the results of user assessment, obtained an average score of 3.3 with a good category. Thus, this media is suitable for use.